Could Change. A Word Composition: “Phantom Words” and the Aesthetics of Speech-Loops - Matter, Marc (eLyra: Revista da Rede Internacional Lyracompoetics, 2023)
This paper investigates the aesthetics and cognitive effects of speech-loops in relation to my own word composition Could Change (2022) by means of artistic research in combination with a transdisciplinary approach including input from literary studies, media and sound studies, musicology and psychology. I relate my definition of a loop – a short repetitive cycle of identical material, iterated for a supposedly innumerable time – to my word composition which consists of textual fragments of news-headlines spoken by a tweaked synthetic voice. Could Change is based on speech-loop as its main structural feature, realized by a custom-made algorithm. To provide a context, I will also present and describe a few selected examples of works in the field of sound poetry that highly depend on loops. I will show that loops have a particularly strong aesthetic impact, because of its mechanical precision and its short-durational cycles: Loops exploit the aesthetic effects of extreme repetition to generate pounding rhythms and are able to alter the time-axis from linear to circular, resulting in an ambiguous state between vivid movement and deadlock. The aesthetic effects of speech-loops will be put in relation to sound and musicality, but also to the textual level and semantics. This includes the emptying of meaningful content of a speech-loop (‘semantic satiation’), lexical hallucinations and apophenia effects like ‘phantom words’, a term and concept introduced by psychologist Diana Deutsch. In Could Change all of these features are highly relevant. I will therefore provide an insight into the original idea to compose this work, as well as into its production process. I conclude with the acknowledgement of the concept of a loop as a self-reliant, independent compositional feature that complicates the semantic level and enhances the musicality of sound poetry.